2021
DOI: 10.1136/jitc-2021-003351
|View full text |Cite
|
Sign up to set email alerts
|

Epitope spreading driven by the joint action of CART cells and pharmacological STING stimulation counteracts tumor escape via antigen-loss variants

Abstract: BackgroundTarget antigen (Ag) loss has emerged as a major cause of relapse after chimeric antigen receptor T (CART)-cell therapy. We reasoned that the combination of CART cells, with the consequent tumor debulking and release of Ags, together with an immunomodulatory agent, such as the stimulator of interferon gene ligand (STING-L) 2′3′-cyclic GMP-AMP (2′3′-cGAMP), may facilitate the activation of an endogenous response to secondary tumor Ags able to counteract this tumor escape mechanism.MethodsMice bearing B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…CAR T cells recognizing the gp75 mouse melanosomal antigen have been described. 61 The CAR construct carries an EGFP reporter gene to monitor the gene transfer of splenocytes that were preactivated with anti-CD3 and anti-CD28 mAbs. CAR gene transfer attained over 90% transduction efficiency using a retroviral vector ( Figure S9 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAR T cells recognizing the gp75 mouse melanosomal antigen have been described. 61 The CAR construct carries an EGFP reporter gene to monitor the gene transfer of splenocytes that were preactivated with anti-CD3 and anti-CD28 mAbs. CAR gene transfer attained over 90% transduction efficiency using a retroviral vector ( Figure S9 A).…”
Section: Resultsmentioning
confidence: 99%
“…Retroviral generation was performed as previously reported. 61 Briefly, isolated CD8 T cells from splenocytes were activated in 24-well plates (Cellstar) coated with anti-CD3 mAb (2 μg/mL, clone 17A2, Biolegend) and supplemented with soluble anti-CD28 mAb (1 μg/mL, clone 37.51, Biolegend) for 48 h in complete medium supplemented with human IL-2 (50U/ml) (Proleukin) at 10 6 /mL density. After 48 h later, lymphocytes were resuspended in retrovirus supernatant containing protamine sulfate (10 μg/mL, SIGMA) and human IL-2 and were spin-inoculated at 2000 x g for 90 min at 32°C.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Woo et al 15 showed that the stimulator of interferon genes mechanism can be upregulated by neoantigen presentation, triggering dendritic cell activation, presentation to CD8 T cells, type I interferon production, and tumor microenvironment infiltration of T cells. Based on this, Conde et al 16 combined chimeric antigen receptor T cell therapy and treatment with the immunomodulatory agent 2′3′-cGAMP in preclinical murine melanoma models to improve tumor microenvironment modulation and enhance epitope spreading with stimulator of interferon genes-L/ligand. This led to tumor growth suppression and improved OS in these murine models, with abscopal effects on distal non-injected lesions.…”
Section: Tangible Evidence Of the Abscopal Phenomenonmentioning
confidence: 99%
“…In conclusion, lung cancer presents a substantial challenge to the development of effective CAR-based immunotherapies. Nonetheless, advanced genetic engineering technologies that allow precise delivery of cells to the site of disease, recognition of a desired target portfolio, re-education of the immunosuppressive TME and also the stimulation of endogenous immune reactivity and epitope spreading [123][124][125][126][127] together offer hope for future success in this daunting quest.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%